Entamoeba histolytica: Gene Expression Analysis of Cells Invading Tissues - Helen C. Fernandes; Ana F. Costa; Michelle A. R. Freitas; Almir S. Martins; Jorge L. Pesquero; Élida M. Rabelo; Maria A. Gomes (The Scientific World Journal)
Entamoeba histolytica is a protozoan parasite that presents a risk to the health of millions of people worldwide. Due to the existence of different clinical forms caused by the parasite and also different virulence levels presented by one strain, one would expect differences in the profile of gene transcripts between virulent and nonvirulent cultures. In this study we used the differential display to select gene segments related to invasiveness of amoeba. One Brazilian strain of E. histolytica in two conditions, able or not to cause lesions in experimental animals, was used. RNA from this strain, was used to study the differential expression of genes. 29 specific gene fragments differentially expressed in the virulent strain were selected. By real-time PCR, six of these genes had confirmed their differential expression in the virulent culture. These genes may have important roles in triggering invasive amoebiasis and may be related to adaptation of trophozoites to difficulties encountered during colonization of the intestinal epithelium and liver tissue. Future studies with these genes may elucidate its actual role in tissue invasion by E. histolytica generating new pathways for diagnosis and treatment of amoebiasis.